The contribution of the study journal for teaching in Visual Arts (Revista Apotheke, 2022)
This text discusses the relevance of using the journal as a research tool in the teaching and learning process in Visual Arts. Through written or visual records, we seek a greater understanding of the theoretical and practical processes of the subject in training, in this case, high school students, from the State Elementary School Leonor de Barros, in Florianópolis (SC). Since the journal is a form of documentation and organization of ideas, thoughts, plans and studies, we investigate, through the Qualitative Methodology, the possibility of a continuous self-assessment and reflection of students' experiences in the field of art and life, aiming at an educational action in Visual Arts, more critical and reflective.
Keywords: Journal; experience; teaching of Visual Arts